Fear of Missing Out as a Reflection of Generation Z’s Participatory Culture: A Study of Slang Forms Among TikTok Users in Indonesia - Putri Oktarin Nadya; Muhammad Safwan Jamil; Arie Azhari Nasution; Prayogo Prayogo; Putri Utami (Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
This study examines the phenomenon of Fear of Missing Out (FoMO) as a reflection of GenerationZ’s participatory culture through the use of slang on the TikTok platform in Indonesia. Theoretically,this study is grounded in the sociolinguistic perspective of Chaer and Agustina (2010), whichemphasizes that language is variable according to heterogeneous social contexts. Within thisframework, slang is understood as part of a dynamic sociolect and functions as a marker of groupidentity. The analysis employs the classification of slang forms by Allan and Burridge (2006) namely,fresh and creative, flippant, imitative, acronym, and clipping which is relevant for explainingGeneration Z’s linguistic adaptations in responding to the demands of fast-paced and aestheticallydriven digital communication. This study employs a qualitative netnographic approach withparticipatory observation of trending content from March 2024 to December 2026. Data consisting ofcaptions, video transcripts, and comments were selected through purposive sampling based oncriteria of virality, interaction intensity, and representation of slang forms until data saturation wasreached. The results of the study revealed 15 instances of slang categorized into four types accordingto Allan and Buridge (2006): 4 instances of “fresh and creative,” 3 of “flippant,” 4 of “acronyms,”and 4 of “clippings.” The research findings also indicate that the use of slang serves not only as acommunication tool but also as a performative strategy to maintain social existence amid FoMOpressures, aligning with Eckert’s (2019) perspective on language as a practice of identity negotiationin digital society.